Pemberdayaan perempuan melalui ormas Islam wanita di Kota Serang - Maisaroh, Ima; Mahpudin, Mahpudin; Stiawati, Titi (Universitas Negeri Malang, 2025)
Women’s empowerment through Islamic women’s organizations in Serang City Women’s Islamic organizations (Muslimat, Aisiyah, and Persistri) in Serang City have significantly increased women’s involvement in the public sphere. Although religiously based, these organizations implement strategic programs in non-religious sectors to strengthen women’s empowerment. Their efforts focus on addressing gender inequality and the strong patriarchal culture in Serang City while promoting the message that Islam supports gender equality and women’s independence. This study examines the contributions of Islamic women’s organizations, including Aisyiyah Muhammadiyah, Muslimat NU, and Persistri Persis, in empowering women in Serang City. The research employs an exploratory and developmental social method with a quantitative descriptive approach. The findings indicate that these organizations engage in religious activities and play a crucial role in women’s empowerment through various programs. The study concludes that there is significant potential for synergy between these organizations and other stakeholders to strengthen women’s empowerment further. Organisasi Islam perempuan (Muslimat, Aisyiyah, dan Persistri) di Kota Serang telah memberikan dampak yang signifikan dalam meningkatkan keterlibatan perempuan di ranah publik. Meskipun berbasis keagamaan, organisasi ini melaksanakan program-program strategis di sektor non-keagamaan untuk memperkuat pemberdayaan perempuan. Upaya mereka berfokus pada mengatasi ketimpangan gender dan budaya patriarki yang masih kuat di Kota Serang, sekaligus menyampaikan pesan bahwa Islam mendukung kesetaraan gender dan kemandirian perempuan. Penelitian ini mengkaji kontribusi organisasi Islam perempuan, termasuk Aisyiyah Muhammadiyah, Muslimat NU, dan Persistri Persis, dalam memberdayakan perempuan di Kota Serang. Penelitian ini menggunakan metode sosial eksploratif dan pengembangan dengan pendekatan deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa organisasi-organisasi ini tidak hanya berfokus pada kegiatan keagamaan, tetapi juga berperan penting dalam pemberdayaan perempuan melalui berbagai program. Studi ini menyimpulkan bahwa terdapat potensi besar untuk sinergi antara organisasi-organisasi ini dengan berbagai pemangku kepentingan lainnya guna semakin memperkuat pemberdayaan perempuan.